Does Islamic Financing Drive Economic Growth? Evidence from Indonesia - Laiya, Sukrin; Muhamad Said Fathurrohman (Universitas Airlangga, 2024)
This study aims to determine the role of Islamic banking in supporting Indonesia's economic growth. Islamic banking is represented by Islamic financing variables, while economic growth is represented by gross domestic product. In addition, this study uses three control variables, namely inflation, investment, and trade ratio. The data used in this study are quarterly data from the period 2010Q1 to 2022Q4, and the method used is the Vector Error Correction Model (VECM). The findings of this study are that in the short term and long term, Islamic financing does not significantly affect GDP. This is because the type of financing provided by Islamic banks is more consumptive than productive. Meanwhile, inflation and trade ratio have a negative and significant effect on GDP in the long run. Meanwhile, investment has a positive and significant effect on GDP in the long run.